Dementing brain processes in patients with Wilson’s disease and multiple sclerosis (pathogenesis and treatment approaches) - Волошин-Гапонов, Іван Костянтинович; Гапонов, Петро Костянтинович (Psychiatry, Neurology and Medical Psychology, 2019)
This article discusses various aspects of dementing processes in patients with Wilson’s disease (WD) and multiple sclerosis (MS), followed by a discussion of current pathogenetic treatment methods for these patients. A comprehensive clinical and laboratory study showed that the pathogenesis and staged development of the dementing process in patients with WD and MS largely coincides with those in patients with Alzheimer’s disease and depends on three groups of factors: genetic predisposition, natural (biological) aging, and endo and exogenous pathogenic factors effects on the brain. Therefore, on the basis of the data presented by us, as well as literature data, it allows us to state that dementia is an organic pathophysiological syndrome of destruction of the critical mass of structural-functional blocks and systems of cognitive mechanisms of the brain. Each individual has his own, genetically determined, critical mass of cognitive mechanisms. Like any false system, this one is ultimately subject to both natural (slow) decay and pathological (accelerated) decay due to the death of neurons both in the type of apoptosis and in the type of necrosis. Thus, in patients with WD and MS, the pathogenetic process always involves structures sooner or later that ensure the functioning of the cognitive functions of the brain and lead to the development of their defects, therefore, therapy should be prescribed for the treatment of these patients. Dementia should be treated at its early stage, at the stage of cognitive impairment (CI). The general principles of managing patients with CI are the determination of the etiopathogenetic cause underlying the development of cognitive impairment, the reduction in the degree and prevention of the progression of cognitive deficit and the impact, if possible, on risk factors. Also, at all stages of cognitive deficiency, treatment of concomitant somatic diseases and correction of the emotional state are relevant. Therefore, timely prescribed comprehensive, pathogenetically substantiated personified therapy helps prevent irreversible consequences and improves the quality of life of patients.